Proposition of DTC model for knowledge management in information technology consulting enterprises - Oliveira, Paulo Sergio Gonçalves de; Lopes, Meire dos Santos; da Silva, Luciano Ferreira; Silva, Dirceu da (Revista de Administração da UFSM, 2015)
This paper aims to purpose inside knowledge management framework the main practices to promote information technology professionals learning. The theoretical basis for this study was Organizational Learning models by Peter Senge (2001). This model correlates communities of practice and knowledge transfer models to promote individual and organizational learning these aspects motivates researchers to namely the model as DTC. The objective was achieved using a survey developed with 164 TI Professionals which works in consulting firms in Sao Paulo Regions using PLS-PM statistical tool which determinates the variables are import for professionals learning. The statistical model highlighted Personal Mastery, Knowledge Transfer and Communities of Practices as main factors for this TI professionals learning and knowledge exchange, these aspects motivates the researchers to put the name DTC in model. By the way this study is an important tool for enterprises or researchers which wants to import organizational learning practices using knowledge management framework.